Improvement of Creative Thinking Ability through Problem-Based Learning with Local Culture Based on Students’ Gender and Prior Mathematics Ability - Ramadhani, Rahmi; Farid, Fajri; Lestari, Fitria; Machmud, Amir (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
The purpose of this study was to determine the increase of students' creative thinking, which taught using problem-based learning with local culture (PBL-Local Culture). In this study also saw the interaction between students' gender and students' prior mathematics ability. This type of research is quasi-experiment research, using pre-test post-test control group design. Data were analyzed using SPSS 25 through Two-Way ANOVA. The result shows that increasing the creative thinking abilities of students taught using problem-based learning with local culture is significantly higher than the creative thinking abilities of students taught using classical learning. Based on the result, we found that the use of problem-based learning local culture (PBL-Local Culture) offered the opportunity to give student new experience to solving real problems in their daily life, primarily related in their local culture. Students can describe how to solve the daily life problem with mathematically modelling. This learning model has given the facility to students at the end to improve their creative thinking ability. Students make the new model of problem-solving and finally they can solve that problem with their model. This study also found that the factor of students' gender and students' prior mathematics ability has not given the effect of students' creative thinking ability. It means that there is no gap in gender and the contribution of students' prior mathematics ability in students' academic skills. Based on this study, we recommendation of this model to using in other subjects in the learning class and to improving other learning ability, not limited in creative thinking ability.